In the face of hypothetic civilization. Spaemann, (post)modernity, postsecularism - Szkaradnik, Katarzyna (Hybris, 2015)
Robert Spaemann is one of the leading contemporary philosophers whose thought is focused on Christian ethics. Despite his bonds with the Catholic Church he does not use philosophy to “prove” a doctrine but proposes individual ideas avoiding reductions. His reflections on people’s naturalness and historicity, teleology, paradoxicality of science do not lead to simple solutions but are the consequence of participation in the society of contingency. The authoress of this sketch considers if Spaemann’s thought could be inspiring for non-Catholics, as well as ponders over its connections with postsecularism, working out the modernity in respect of religiosity. This article shows what appears from his interpretations to the critical members of (post)modern society and where today is a place for heading for “the immortal rumor”. The authoress explains how Spaemann argues for the potential of anthropomorphic view and human ability to go beyond himself – which does not lead into nothingness.